2019
DOI: 10.1111/1462-2920.14733
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a universal set of primers to study animal‐associated microeukaryotic communities

Abstract: Summary The application of metabarcoding to study animal‐associated microeukaryotes has been restricted because the universal barcode used to study microeukaryotic ecology and distribution in the environment, the Small Subunit of the Ribosomal RNA gene (18S rRNA), is also present in the host. As a result, when host‐associated microbial eukaryotes are analysed by metabarcoding, the reads tend to be dominated by host sequences. We have done an in silico validation against the SILVA 18S rRNA database of a non‐met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…kit following manufacture instructions including blank extractions to control for (cross-) contamination events. DNA extractions were then amplified in triplicates using the universal Eukaryotic V4 tagged primers TAReuk454FWD1 (5'-CCAGCA(G⁄C)C(C⁄T)GCGG-TAATTCC-3') and TAReukREV3 (5'-ACTTTCGTTCTTGAT(C⁄T)(A⁄G)A-3') (Stoeck et al, 2010) that amplify only eukaryotes and offer a good taxonomic resolution across the entire eukaryote realm (del Campo et al, 2019). Each tagged PCR primer consists of a unique tag sequence of 8 nucleotide appended to the 5'end of the common amplification primer sequence.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…kit following manufacture instructions including blank extractions to control for (cross-) contamination events. DNA extractions were then amplified in triplicates using the universal Eukaryotic V4 tagged primers TAReuk454FWD1 (5'-CCAGCA(G⁄C)C(C⁄T)GCGG-TAATTCC-3') and TAReukREV3 (5'-ACTTTCGTTCTTGAT(C⁄T)(A⁄G)A-3') (Stoeck et al, 2010) that amplify only eukaryotes and offer a good taxonomic resolution across the entire eukaryote realm (del Campo et al, 2019). Each tagged PCR primer consists of a unique tag sequence of 8 nucleotide appended to the 5'end of the common amplification primer sequence.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…A hybrid approach is to develop primers that work on a wide taxonomic range of eukaryotes but exclude all or most metazoans. One such set of primers developed to look at parasites (Bower et al, ) has recently been shown to work on a wide range of microeukaryotes associated with taxonomically diverse animal hosts (del Campo et al, ). Extensive deployment of these methods will certainly help to identify the main questions to ask about the eukaryome, many of which are currently not even clear.…”
Section: The Eukaryome Within the Microbiomementioning
confidence: 99%
“…up to 92% in coral, 42% in krill, and 45% in fish) [57,72,63]. This approach also requires designing and optimizing the blocking-primers for each animal host, which remains a challenge [71][72].…”
Section: Introductionmentioning
confidence: 99%